Occupational Exposure and Ventilation Assessment in New York City Nail Salons. Issue 5 (8th April 2020) - Harrichandra, Amelia; Roelofs, Cora; Pavilonis, Brian
Abstract: In 2015, New York State enacted new ventilation regulations to protect employees and clients from exposure to chemicals used in nail salons. This study measured common air pollutants found in nail salons and assessed compliance with ventilation requirements. Area sampling was conducted in 12 nail salons located in New York City for three consecutive days (Thursday, Friday, and Saturday) to measure total volatile organic compounds (TVOCs), methyl methacrylate, toluene, and ethyl acetate concentrations and estimate ventilation rates. Salon characteristics were determined through a walkthrough inspection and survey administered to the manager. The average daily concentration of carbon dioxide and TVOCs across all salons was 1070 ppm [standard deviation (SD) = 440 ppm] and 29 ppm (SD = 25 ppm), respectively. Chemical-specific air sampling showed low to non-detectable levels of the three measured chemicals. Seventy-five percent of the nail salons did not meet general minimum outdoor airflow requirements. Little temporal variation was observed in day-to-day average concentrations of contaminants within salons, indicating uniform exposure during high customer count days. Salons that met the outdoor airflow requirements had twice the average daily customers (83 versus 42) and half the TVOC concentrations compared with salons that did not (33 versus 16 ppm). Nail salons not meeting ventilation requirements tended to have fewer customers and managers that did not understand the essential components of the ventilation system. Data from this study can be used as evidence of reduction in exposure due to compliance with the ventilation requirements.